SAT0518 Low Back Pain Prevalence in Italian Adolescents and Its Association with Quality of Life. (15th July 2016) - Bakdounes, L.; Galozzi, P.; Maghini, I.; Oliviero, F.; Caputo, E.; Chia, M.; Ermani, M.; Masiero, S.; Punzi, L.
Abstract : Background: Low Back Pain (LBP) is a very common health problem that affects people of all ages. It has profound effects on well-being and is often the cause of significant physical and psychological disability. Until now, very few studies have investigated these aspects in adolescents 1 . Objectives: To define the prevalence and the characteristics of LBP in high school adolescents from the city of Venice (Veneto region, Italy) and to investigate its impact on disability, lifestyle and quality of life (QoL). Methods: The cross-sectional study included 145 students (89 females and 56 males) with a mean age of 15.9 ± 0.72 years that completed the Short Form 36 Questionnaire (SF-36) for QoL assessment and a structured questionnaire concerning anthropometric data and participants' characteristics as well as the symptoms prevalence, duration and treatment, health provider consultation, and referral for diagnostic tests. For normally distributed variables the Student T test was used while, for categorical variables, the Pearson's Chi Square was performed. Results: Among the 145 subjects included in the study, 82 (56.5%) referred having experienced LBP: 8.2% at the moment of survey, 27.6% in the past with complete resolution of the symptoms, and 20.7% in the past without symptoms resolution. Females experienced LBP significantly more frequently than males (52.2% versus 47.8%, p<0.05). There was no association between LBP and age or physical activity. 59.0% of the adolescents with LBP had sought medical evaluation and the 47.3% of this group had been referred for diagnostic tests. Concerning pain resolution, 78.9% of positive resolved respondents did not take any actions while, out of the total number of subjects involved, 58.3% used drugs, 60.0% recurred to rehabilitation and 20.0% combined drugs and rehabilitation. This latter category was also more sceptical than the others (p=0.016) about the future possibility of solving LBP, confirmed by lower QoL scores, although it was the most interested in participating to a prevention program (p=0.04). Furthermore, there was a strong correspondence between the QoL of the students that experimented LBP only in the past and the QoL of those who had never suffered of LBP in their lives. Conclusions: Our study confirmed that LBP is frequent in Italian adolescents and that a large number of subjects consult a healthcare service 1 . The results highlighted the strong impact of LBP on QoL, leading to significant physical and psychological health issues. According to our data, SF 36 may be a reliable tool to describe the QoL modifications related to the presence of pain. Further investigations are necessary to understand the inverse association observed between therapy and pain resolution. References: Masiero S., Acta Pædiatrica, 2008 Acknowledgement: This study was supported by HEMOVE - Health and Motion Venice Association. Disclosure of Interest: None declared